Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2151/jmsj.2017-024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Tropical Cyclone Intensity and Structure Using Upper Tropospheric Atmospheric Motion Vectors

Abstract: 21The high temporal and spatial resolutions of geostationary satellite observations achieved by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…Retrieval methods for AMVs were developed in the early 1960s (e.g., Menzel 2001), and are being still updated through advanced sensor technologies and/or the adoption of new algorithms (e.g., Velden et al 2005). AMVs provide unique information for TC analysis and monitoring, even though vertical distributions of AMV datasets are biased in the upper level (e.g., Oyama 2017;Oyama et al 2018). The present investigation used AMVs which were retrieved every 10 min from Himawari-8 TC target observations with a time interval of 5 min (Bessho et al 2016;Oyama et al 2018).…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieval methods for AMVs were developed in the early 1960s (e.g., Menzel 2001), and are being still updated through advanced sensor technologies and/or the adoption of new algorithms (e.g., Velden et al 2005). AMVs provide unique information for TC analysis and monitoring, even though vertical distributions of AMV datasets are biased in the upper level (e.g., Oyama 2017;Oyama et al 2018). The present investigation used AMVs which were retrieved every 10 min from Himawari-8 TC target observations with a time interval of 5 min (Bessho et al 2016;Oyama et al 2018).…”
Section: Data Descriptionmentioning
confidence: 99%
“…AMVs provide unique information for TC analysis and monitoring, even though vertical distributions of AMV datasets are biased in the upper level (e.g., Oyama 2017;Oyama et al 2018). The present investigation used AMVs which were retrieved every 10 min from Himawari-8 TC target observations with a time interval of 5 min (Bessho et al 2016;Oyama et al 2018). The retrieval scheme was developed by the Meteorological Satellite Center of the Japan Meteorological Agency, and…”
Section: Data Descriptionmentioning
confidence: 99%
“…AMVs are normally derived using the cross‐correlation method (Leese et al, 1971; Schmetz et al, 1993). Even the state‐of‐the‐art AMV products do not cover TC's inner core region (Oyama et al, 2018), presumably because the operational methods do not treat rotation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study it will be demonstrated that shorter sampling times and continuous rapid scanning combined with the advanced sensors on these newgeneration satellites will substantially improve the quality and quantity of the AMVs, and thus their potential impacts on the U.S. Navy regional and global model analyses and predictions. Oyama (2017) has demonstrated that composites of TC outflows at the cloud tops computed from AMVs can be related to the intensification rates. Oyama et al (2018) then compare the maximum tangential winds in the outflow estimated from 30-min-interval Himawari-8 target observations with the maximum surface wind evolutions throughout the lifetime of two typhoons and suggest that Himawari-8 AMVs can be used to monitor TC intensification and related structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Oyama (2017) has demonstrated that composites of TC outflows at the cloud tops computed from AMVs can be related to the intensification rates. Oyama et al (2018) then compare the maximum tangential winds in the outflow estimated from 30-min-interval Himawari-8 target observations with the maximum surface wind evolutions throughout the lifetime of two typhoons and suggest that Himawari-8 AMVs can be used to monitor TC intensification and related structural changes.…”
Section: Introductionmentioning
confidence: 99%